From poverty to common prosperity: an evaluation of agricultural-cultural-tourism integration and its impact on economic growth - Shi, Lidong; Liao, Xiujian (Frontiers in Sustainable Food Systems, 2025)
The integration of agriculture, culture, and tourism industries as a driver of industrial modernization has become an essential strategy during China’s transition from rapid growth to high-quality development. In pursuit of the goal of common prosperity, local governments at various levels have actively responded by attempting to promote economic growth through the integration of these three industries. Data of 126 key national rural revitalization counties in China between 2018 and 2020 is selected as the sample, and an entropy value analysis is used, this paper discusses the integration level of agriculture, culture, and tourism industries in these counties and whether such integration has promoted local economic growth. The results show that while the integration level of these industries in key rural revitalization counties has seen fluctuating growth, the overall level remains low with significant disparities across regions. Counties with higher economic development, higher human capital, and higher digitalization levels tend to have higher integration levels of agriculture, culture, and tourism industries. However, compared to ethnic counties, non-ethnic counties, despite their disadvantage in ethnic culture, have achieved rapid growth and caught up in the integration of these industries by adapting to local conditions and leveraging local features. Further analysis indicates that even though the current integration level in these counties is not high, it still promotes local economic growth. The conclusions provide insights for counties transitioning from poverty alleviation to rural revitalization. By promoting the integrated development of agriculture, culture, and tourism industries, these counties can achieve economic growth, narrow regional development gaps, and ultimately realize the goal of common prosperity.